EFEKTIVITAS PEMANGGILAN GHAIB TERHADAP PERKARA PERCERAIAN DI PENGADILAN AGAMA (Studi Kasus pada Pengadilan Agama Kelas 1 A Watampone) - Jamaluddin T (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2018)
One of important duty of Justice of Religion is execute denominating to be suedunknown of its recidence so its rightss fufilled. In section 27 ( 1) Regulation ofGovernment of Number 9 Year 1975 mentioning that If recidence sued unknownor ill defined or don't have recidence which remain to like the in Section 20sentence ( 2), call done by gluing suing at pasteboard in Justice and announcing itthrough one or some other mass media or newspaper which specified by Justice.Denominating of ghaib in Justice of Religion of Watampone, since ahead hithertostill use radiogram media (radio Suara Daya Indah Bone), a media broadcasting ofold and first public in Bone. From other side Radio media, Justice of Religion ofWatampone also paste up the the writ [in] pasteboard, not yet used other medialike social media and newspaper which use facility of internet which [is] likedmore notabene and used by society in this time. Radio of SDI its broadcast reachnot yet reached all region of Bone particularly again entire/all Indonesia region.Case of occult is sued case or requesting of unknown address or him categoricallyin all Indonesia region. Data of Young Fiscal clerk of Suing, that amount of caseof ghaib every year + 200 case. Year 2016 243 case, while January - August 2017amounting 138 case. Result of incoming denominating next to nothing becausedenominating, but just because notification of its family or others.